Settlement of Corporate Crime with Restorative Justice Approach - Manurung, Gydeon Irmawan; Martono Anggusti; July Esther (Journal of Legal and Cultural Analytics, 2025)
The resolution of corporate criminal offences with a restorative justice approach is an alternative effort in resolving cases involving corporations, which does not only focus on punishment, but also on restoring relationships between the parties involved, as well as efforts to repair the negative impacts caused by the criminal act. In the corporate context, this means that companies involved in criminal offences are not only subject to legal sanctions, but are also required to take social and moral responsibility for the harm caused, both to individuals, society and the environment. This approach has the potential to improve a company's reputation, minimise long-term social impacts, and encourage more ethical and responsible corporate practices. Restorative justice also provides space for companies to make internal improvements, such as reforming policies and procedures that can prevent the recurrence of similar criminal offences in the future. Thus, the resolution of corporate criminal offences through a restorative justice approach not only provides solutions for victims and perpetrators, but also contributes to the development of a more just and sustainable law.